Genetic Differentiation and Relationships of Populations in the Cycas balansae Complex (Cycadaceae) and its Conservation Implications - XIAO, LONG-QIAN (Oxford University Press, 2006)
• Background and Aims The Cycas balansae complex is arguably a controversial group with regard to species delineation. Some taxonomists recognize a single polymorphic species while others distinguish five narrowly defined ones. The unresolved taxonomy has the potential to bring about significant problems for species conservation. Thus, an investigation to examine the genetic diversity and differentiation in the C. balansae complex was performed to determine the relationship of populations and to test whether the morphologically defined segregations represent genetically distinct units. • Methods Inter-simple sequence repeat (ISSR) markers were employed to assess the genetic diversity in the C. balansae complex with a sample of 158 individuals from all extant populations in China. • Key Results ISSR markers revealed low genetic diversity in all populations studied (H(E) and H(O) averaged 0·0639 and 0·0798 at the population level, respectively). Phenetic analysis showed that the C. balansae complex grouped into five clusters closely corresponding to the narrowly defined C. balansae, C. parvula, C. shiwandashanica, C. tanqingii and C. simplicipinna. • Conclusions ISSR data suggest that the C. balansae complex has evolved into five genetically distinct units. These might be derived from a relatively widespread common ancestor through multiple vicariant events including geographical isolation resulting from the collision of the Indian plate with the Eurasian plate and from Pleistocene glaciations. In conservation, attention should be paid to each genetic unit.